2013
DOI: 10.1007/s10964-013-0010-x
|View full text |Cite
|
Sign up to set email alerts
|

Youths’ Substance Use and Changes in Parental Knowledge-Related Behaviors During Middle School: A Person-Oriented Approach

Abstract: Parental knowledge is a key protective factor for youths’ risky behavior. Little is known about how longitudinal combinations of knowledge-related behaviors are associated with youths’ substance use. This longitudinal study uses Latent Transition Analysis to identify latent patterns of parental knowledge-related behaviors occurring in mother-youth dyads during middle school and to investigate how changes in knowledge-related patterns are associated with youths’ substance use in Grade 6 and the initiation of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 45 publications
2
42
0
1
Order By: Relevance
“…For example, in adolescent mental health assessments, we have found that when two parents (i.e., informants who observe adolescents in the same context) converge on reports of relatively high adolescent mental health concerns, the adolescent both displays greater hostility within observed family interactions, and self-reports greater mental health concerns, relative to adolescents whose parents do not converge in their reports about adolescent mental health (De Los Reyes et al 2016a). Consistent with this work in mental health, in recent developmental work, adolescentparent dyads that converge on relatively low levels of parental knowledge have adolescents who are at particularly high risk for developing substance use (e.g., Lippold et al 2013Lippold et al , 2014. Consequently, sometimes convergence between reports may serve as a marker for factors that pose risk for the development of adolescent maladjustment (Fig.…”
Section: Converging Operations: When Adolescents' and Parents' Reportmentioning
confidence: 83%
See 4 more Smart Citations
“…For example, in adolescent mental health assessments, we have found that when two parents (i.e., informants who observe adolescents in the same context) converge on reports of relatively high adolescent mental health concerns, the adolescent both displays greater hostility within observed family interactions, and self-reports greater mental health concerns, relative to adolescents whose parents do not converge in their reports about adolescent mental health (De Los Reyes et al 2016a). Consistent with this work in mental health, in recent developmental work, adolescentparent dyads that converge on relatively low levels of parental knowledge have adolescents who are at particularly high risk for developing substance use (e.g., Lippold et al 2013Lippold et al , 2014. Consequently, sometimes convergence between reports may serve as a marker for factors that pose risk for the development of adolescent maladjustment (Fig.…”
Section: Converging Operations: When Adolescents' and Parents' Reportmentioning
confidence: 83%
“…As mentioned previously, prior work points to substantial dyad-level variations in magnitudes of convergence, including informant dyads who converge quite highly in reports of psychological phenomena (e.g., De Los Reyes et al 2009, 2013a, 2016aLippold et al 2011Lippold et al , 2013Lippold et al , 2014. What might convergence between these reports reflect?…”
Section: Converging Operations: When Adolescents' and Parents' Reportmentioning
confidence: 90%
See 3 more Smart Citations